Schiff base anchored silver nanomaterial: An efficient and selective nano probe for fluoride detection in an aqueous medium. (2021) - Swami, Suman; Sharma, Neelam; Agarwala, Arunava; Shrivastava, Vibha; Shrivastava, Rahul
Abstract: Schiff base anchored plasmonic silver nanomaterial was designed and developed as a qualitative nano probe for fluoride detection in an aqueous medium. Schiff base encloses phenolic functionality has utilized as reducing as well as capping agent for preparation of the silver nanoparticles. The fluoride sensing was investigated by UV–Visible, FSEM and FSEM-EDAX analysis techniques. The UV–Vis and FSEM analysis illustrate that Schiff base anchored silver nanoparticles, exhibited SPR band at 475 nm and uniform spherical (28–30 nm) size which on interaction with fluoride, nanoparticles get agglomerate with a visual color change from brown to dark brown.